Developing and Validating a Model of Quality Management in Order to Implement the Educational Goals of the Document of Fundamental Change in Education - Layla Anbarsetani; Rashid Zoalfaghari Zafarani; BiBi Sadat Miresmaeili; AbasAli Ghayomi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present study was conducted with the aim of developing and validating a quality management model in order to implement the educational goals of the document of fundamental transformation of education and upbringing with a combined approach. In terms of applied purpose, the present research method was a combination of consecutive exploratory type and data collection method in the qualitative part, field using interviews and in the quantitative field using a questionnaire. The statistical population in the qualitative section includes professors of educational management familiar with the document of education and training as well as familiar with quality management, who were purposefully selected as a standard for qualitative interviews on the subject of research (19 interviews with 19 people and up to The theoretical saturation limit continued) and in the second (quantitative) part, after collecting information from qualitative research, a questionnaire was constructed. Therefore, in general, it was found that the categories of strategic quality management model in order to implement the educational goals of the document of fundamental transformation of education and training, in order of importance, including infrastructure, evaluation, finance, human resources, participatory education, communication, human, organizational structure, program is planning and training. The directors of education in the country are recommended to use the results of the present study to achieve the educational goals of the document of fundamental change in education.